Globalisation and inter-occupational inequality: Empirical evidence from OECD countries - Bigsten, Arne; Munshi, Farzana (© 2013 John Wiley & Sons Ltd., 2016)
This article was published in World Economy [© 2013 John Wiley & Sons Ltd.] and the definite version is available at: http://onlinelibrary.wiley.com/doi/10.1111/twec.12128/full The article website is at: http://onlinelibrary.wiley.com/doi/10.1111/twec.2014.37.issue-3/issuetoc